The role of complement factor I rare genetic variants in age related macular degeneration in Finland - Andreadi, Anneliza; Hallam, Thomas M; Brocklebank, Vicky; Sharp, Scott J; Walsh, Patrick R; Southerington, Tom; Hautalahti, Marco; Steel, David H; Lotery, Andrew J; Harris, Claire L; Marchbank, Kevin J; Kavanagh, David; et al. (Oxford University Press (OUP), 2025)
Age-related macular degeneration (AMD) is the leading cause of irreversible blindness in the developed world. The alternative pathway (AP) of complement has been linked to the pathogenesis of AMD. In particular, rare variants (RVs) in the complement factor I (CFI) gene encoding the Factor I (FI) protein confer increased AMD risk. The prevalence of CFI RVs are well characterised in European AMD, however little is known about other populations. The Finnish population underwent genetic restriction events which have skewed allele frequencies in unexpected ways. A series of novel or enriched CFI RVs were identified in individuals with dry AMD from the Finnish Biobank Cooperative (FINBB), but the relationship between these genotypes and contribution to disease was unclear. Understanding how RVs impact the ability of FI to regulate the complement system is important to inform mechanistic understanding for how different genotypes contribute to disease development. To explore this a series of in vitro assays were used to functionally characterise the protein products of 3 CFI RVs enriched in FINBB dry AMD, where no prior data were available. The G547R variant resulted in almost complete loss of both classical pathway and AP regulatory potential. The c.982 g>a variant encoding G328R FI perturbed an exon splice enhancer site which resulted in exon skipping and a premature stop codon in vitro and low levels of FI in vivo. Despite detailed analysis no defect in levels or function was demonstrated in T107A. Functional characterization of all Finnish CFI RVs in the cohort allowed us to demonstrate that in Finnish dry AMD, collectively the type 1 CFI RVs (associated with FI haploinsufficiency) were significantly enriched with odds ratio (ORs) of 72.6 (95% confidence interval; CI 16.92 to 382.1). Meanwhile, type 2 CFI RVs (associated with FI dysfunction) collectively conferred a significant OR of 4.97 (95% CI 1.522 to 15.74), and non-impaired or normal CFI RV collectively conferred an of OR 3.19 (95% CI 2.410 to 4.191) although this was driven primarily by G261D. Overall, this study for the first time determined the ORs and functional effect for all CFI RVs within a Geographic Atrophy (GA) cohort, enabling calculations of combined risk scores that underline the risk conferred by type 1 and 2 CFI RVs in GA/AMD.